RELATIONSHIP BETWEEN NON PERFORMING LOANS (NPL), CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) TOWARDS RETURN ON EQUITY (ROE) AT PT. BANK CENTRAL ASIA 2014 – 2018 - Achda Vellanita; I Gede Arimbawa; Elok Damayanti (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the relationship of variable NPL with ROE, CAR variable with ROE, and variable LDR with ROE. This research is associative with a quantitative approach. The technique of collecting data uses the documentation and library method, which used a population of quarterly financial statements for 2014-2018 PT BCA Tbk, and it was collected 15 samples. Techniques for analyzing data using SPSS version 16. The results of this study indicate that credit risk (NPL), capital adequacy (CAR), liquidity risk (LDR) have a significant effect on financial performance (ROE). The limitations of the results of this study were only carried out at PT BCA Tbk through secondary data in the form of the 2014-2018 annual financial report. Measurement of Return On Equity (ROE) variables only through independent variables NPL, CAR, and LDR.